Plasma Adenosine Deaminase Enzyme Reduces with Treatment of Pulmonary Tuberculosis in Nigerian Patients: Indication for Diagnosis and Treatment Monitoring (Nigerian Journal of Physiological Sciences, 2021)
Summary: Tuberculosis(TB)-specific host biomarkers for diagnosis and monitoring of treatment response have been identified as priorities for TB research. Macrophage and T cell lymphocytes play vital roles in Mycobacterium tuberculosis immune response and their associated biomarkers could form good candidates for diagnosis and treatment monitoring. The enzyme adenosine deaminase (ADA) is produced mainly by monocytes and macrophages and increase in biological fluids in the course of infection with microorganisms infecting macrophages. This study comprised sixty-eight (68) participants; twenty-four (24) multi-drug-resistant TB(MDR-TB) patients, twenty-four (24) drug-sensitive TB patients(DS-TB) and twenty (20) non-TB apparently healthy individuals. Five (5) milliliters of blood was drawn before commencement of chemotherapy and 6 anti-TB therapy. In DSTB and MDR-TB patients before commencement of chemotherapy and 6 months of anti-TB treatment, the mean plasma levels of ADA were significantly increased compared with control. At 6 months of anti-TB chemotherapy of DSTB or MDR TB patients, ADA level was significantly decreased compared with before chemotherapy. Plasma ADA in DSTB patients before and 6 months of chemotherapy were not significantly different compared MDR TB patients. Plasma ADA level is a promising biomarker for the screening and treatment monitoring of pulmonary tuberculosis but not to differentiate MDR TB from DSTB patients.